Relationship between foot posture and static and dynamic balance in athlete and non-athlete girls - Narmin Ghanizadeh hesar; Marzie Vakili; Behnam Ebrahimi (Biyumikānīk-i varzishī)
Introduction: The aim of this study was to evaluate relationship between foot posture and static and dynamic balance in athlete and non-athlete girls. Material and methods: there were 40 girl student that 20 of them were athlete aged 21/5+- 4/62 and 20non-athlete aged 22/8 +-2/61. to evaluate foot posture, dynamic balance and static balance used radmond,s six scale visual method, star exersion balance test, and BESS test respectively. To analyzing data, indipendent t-test and pearson correlation test was used.(p≤0/05) Results: there was not significant correlation between foot posture with dynamic and static balance in any of athlete and non-athlete girls group (p≥0/05) but there were significant difference in foot posture, dynamic and static balance between two group (p≤0/05). Conclusion:this research show that athletes have a propriate foot posture index and balance function. also we can probably say that fitness and neuro-muscular performance affect on balance more than biomechanic factors such as foot posture. To evaluate this hypothesis we need more researchs.